Taiwanin E Induces Cell Cycle Arrest and Apoptosis in Arecoline/4-NQO-Induced Oral Cancer Cells Through Modulation of the ERK Signaling Pathway - Wang, Shih-Hao; Wu, Hsi-Chin; Badrealam, Khan Farheen; Kuo, Yueh-Hsiung; Chao, Yun-Peng; Hsu, Hsi-Hsien; Bau, Da-Tian; Viswanadha, Vijaya Padma; Chen, Yi-Hui; Lio, Pei-Jei; Chiang, Chung-Jen; Huang, Chih-Yang (Frontiers in Oncology, 2019)
Taiwanin E is a bioactive compound extracted from Taiwania cryptomerioides Hayata. In this research endeavour, we studied the anti-cancer effect of Taiwanin E against arecoline and 4-nitroquinoline-1-oxide-induced oral squamous cancer cells (OSCC) and elucidated the underlying mechanism of action. Basically, OSCC were treated with varying concentration and time interval of Taiwanin E and thereafter analyzed through MTT assay, Flow cytometry, TUNEL assay, and Western blotting. Interestingly, it was found that Taiwanin E significantly attenuated the cell viability of oral cancer cells (T28) in a dose and time dependent manner; nevertheless, no cytotoxic effects were found for normal oral cells (N28). Western blot data suggested that Taiwanin E considerably down-regulated cell cycle regulatory proteins and activated p53, p21 and p27 and induces G1cell cycle arrest in T28 oral cancer cells as evident through Flow cytometry studies. Further, TUNEL and Western blot studies suggested that it induces cellular apoptosis and attenuated p-PI3K/p-Akt survival mechanism in T28 oral cancer cells seemingly through modulation of ERK signaling cascade. Collectively, the present study highlights the prospective therapeutic efficacy of Taiwanin E against arecoline and 4-nitroquinoline-1-oxide-induced oral cancer.